Brazil : Fiscal Transparency Evaluation. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2017)
This report assesses fiscal transparency practices in Brazil in relation to the requirements of the IMF Fiscal Transparency Code. Brazil's practices meet many of the principles of the code at good or advanced levels. Fiscal statistics encompass the general government sector and recognize most of its assets and liabilities. Fiscal reports are published frequently and in a timely manner, and annual financial statements are audited by the Federal Court of Accounts. The transparency of fiscal forecasting and budgeting benefits in some areas from good or advanced practices. The institutional scope of budget documentation is comprehensive, and the key sequences of the budget process are timely.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet